ANALISIS TRANSPORTASI DARAT TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN WAKATOBI - Matoka, Ulfa; Zain, Muhammad; Gunawan, Aldi; Sriningsih, Putri Ayu (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of the study was to analyze the relationship between land transportatioan and economic growth in Wakatobi Regency. This research is included in the type of quantitive research with the analytical method using multiple linear regression, namely examining the vanable relationship between road length and number of motorized vehicles with transportation economic growth in Wakatobi Regency. Result of the analysis the data shows (1) land transportation has a moderate level of linkages to ecomomic growth in Wakatobi Regency, (2) land transportation has an effect of 23,3 percent on the ecomomis growth of transportation in Wakatobi Regency, (3) land transportation has no significant effect on economic growth in Wakatobi Regency and (4) road length has a non-significant positive effect and the number of motorized vehicles has a negative effect on ecomomic growth in Wakatobi Regency.